Use of microarthropods as biological indicators of soil quality: the BSQ sinthetic indicator - Gardi C.; Menta C.; Parisi V. (7. International meeting on Soils with Mediterranean Type of Climate (selected papers), 2002)
The introduction of sustainable development principle has lead to an increasing attention towards concepts such as soil quality and soil health. Soil quality is the ability of soil to function effectively as a component of a healthy ecosystem. Traditional approach to soil quality evaluation was based on the use of physical, chemical and microbiological indicators. Different authors proposed recently new methods for soil quality evaluation, based on soil microarthropods. Soil microarthropods demonstrated to respond sensitively to land management practices and to be correlated with beneficial soil functions. This paper presents two biological indicators of soil quality based on microarthropods and collembola.
7. International Meeting on: Soils with Mediterranean Type of Climate, 2001/09/23-28, Valenzano (Italy)